Comprehensive approaches in group loan management for enhancing women’s economic independence: case study of cetf bandungan district, Semarang regency - Suryani, Wiwik; Inggarwati, Komala (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This study investigates the management of group loans by the Bandungan District Community Empowerment Trust Fund (CETF) to enhance women's economic independence. Specifically, it examines the operational challenges, management strategies, and their impact on beneficiaries. Using a qualitative approach, the research involved in-depth interviews and observations of CETF management (IVCA, Financial Management Unit, Supervisory Body, and Verification Team) and 60 Women's Savings and Loans (WSL) group administrators. The study identifies key obstacles, such as financial instability, behavioral issues among members, and managerial inefficiencies. To address these, CETF implemented mentoring, training, and joint responsibility systems tailored to local contexts. These strategies have resulted in a 98% repayment rate, demonstrating the effectiveness of a community-based microfinance approach. This research is distinctive in its focus on rural women, the use of joint liability mechanisms, and flexible policies, such as loan rescheduling and moratoriums, which are underexplored in prior studies. The findings contribute to the literature on sustainable microfinance and provide practical insights for policymakers and microfinance managers to optimize group loan programs for women's empowerment.